The impact of employee training and development on work productivity in the company - Herdi, Dinda Lia; Haryati, Sri; Nurdiana, Editya (Institute of Computer Science (IOCS), 2025)
Employee training and development is an important component of human resource management, aiming to improve skills, knowledge, and work productivity. This study aims to analyze the influence of training and development on work productivity in SMEs in Indramayu Regency, an area with great potential but still facing various challenges in human resource management. The research method used is a quantitative approach with a descriptive design. Data was collected through a questionnaire to 100 employees from various SMEs who had training and development programs in the last three years. Data analysis was carried out using descriptive statistics, correlation, multiple linear regression, and ANOVA. The results showed that training had a significant influence on work productivity, with a contribution of 45%. Employee development also has a positive impact of 30%, although the contribution is smaller than training. The combination of training and development has a greater influence on work productivity. In addition, the regression model used has a high level of significance (R2=0.52R^2=0.52R2=0.52), which means that 52% of the work productivity variability can be explained by both independent variables. These findings show the importance of synergy between training and development in increasing work productivity. This research makes a practical contribution to SME managers in Indramayu Regency to design more effective and structured training and development policies. Key recommendations include increased investment in technology-based training programs, collaboration with local governments, and the implementation of a sustainable evaluation system. This research is expected to be the foundation for the development of human resources in areas with similar potential